Société Nouvelle d'lndustrie Alimentaire (SONIA), Douala Cameroon: - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Société Nouvelle d'lndustrie Alimentaire (SONIA), Douala Cameroon: 'We have been testing the biscuits described in Philippede Staercke's book Soya but have encountered several problems. 1) The dough obtained from the proportions given is...